A Concept of a Shared Guarantee Trademark in Polish Family Enterprises - Nikodemska-Wołowik, Anna; Bugiera, Konrad (Studia Oeconomica Posnaniensia, 2017)
This article shows the role of a shared guarantee trademark in creating the identity of a family enterprise and presents the results of authors’ own empirical research focused on the evaluation of the aforementioned symbol by Polish buyers. The article fits in the current mainstream discussion between scientists and business practitioners about the significance of family enterprises to the economy in the global sphere. Although the entrepreneur himself/herself was also in the range of authors’ focus, the centre of their attention was the buyer of goods and services offered by Polish family enterprises and marked with a specific trademark. These two perspectives - of a consumer and of an entrepreneur, were crucial to focusing attention on the semiotic and legal aspects of using such a trademark. The result of authors’ consideration is a suggestion of enforcing the family enterprises’ identity and sanctioning family ownership with giving such enterprises a specific symbol by a certifying unit. In the Polish legal system a symbol of this kind is treated as a shared guarantee trademark.